VASYL STEFANYK IN THE FIELD OF HIS READING - Kovalets, Lidiia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
On the basis of primarily epistolary and memoirs, various manifestations of Vasyl Stefanyk’s reading behaviour are considered. It consisted of active searching for books, thoughtfulconversation with texts, deep psychological reactions to some of them, forming his own opinion about them, involving of famous people in reading. It was observed that, given the dynamics and its external manifestations, Stefanyk’s reading action had several stages: the early one, which concerned primary and gymnasium education, the Krakow one, connected with his medical studies at the Jagiellonian University, and the last one (from the 1900s), a period spent mainly on native land. A rich factual material was analysed. It testified that the main segment in the field of Stefanyk’s reading was foreign, primarily Western European literature, especially prose, but also poetry and drama, as well as Ukrainian literature. The author of the «Stone Cross» also had ample opportunities thanks to mastering books in four languages: besides Ukrainian also Russian, Polish and German. The article also attempts to understand the features of the phenomenon of Stefanyk as a reader, which naturally agreed with the psychophysical features of Stefanyk as a man. Reading itself provided writer’s thorough, first of all philological education and turned out to be the same original and productive form of his creative activity as a purely literary work.